Rapid corticosteroid taper versus standard of care for immune checkpoint inhibitor induced nephritis: a single-center retrospective cohort study. Issue 4 (13th April 2021) - Lee, Meghan D; Seethapathy, Harish; Strohbehn, Ian A; Zhao, Sophia H; Boland, Genevieve M; Fadden, Riley; Sullivan, Ryan; Reynolds, Kerry L; Sise, Meghan E
Abstract : Background: Current guidelines for treatment of immune checkpoint inhibitor (ICI)-induced nephritis are not evidence based and may lead to excess corticosteroid exposure. We aimed to compare a rapid corticosteroid taper to standard of care. Methods: Retrospective cohort study in patients with ICI-induced nephritis comparing a rapid taper beginning with 60 mg/day prednisone and tapered to 10 mg within 3 weeks to a historical control group that began 60 mg/day tapered to 10 mg within 6 weeks (standard of care). Renal recovery was defined as creatinine returning to within 1.5-fold baseline. The log-rank test compared the differences in time to renal recovery between the groups. We report rates of renal recovery at 30, 60 and 90 days, and timing and outcomes of ICI rechallenge. Results: Thirteen patients received rapid corticosteroid taper and 14 patients received standard of care. Baseline characteristics were similar between groups. The median time to ≤10 mg/day prednisone was 20 days (IQR 15–25) in the rapid-taper group compared with 38 days (IQR 30–58) in the standard-of-care group. There was no significant difference in the time to renal recovery between the groups, though numerically higher numbers of patients recovered by 30 days, 11 (85%) in the rapid-taper arm versus 6 (46%) in the standard of care arm. Exposure to other nephritis-causing medications (proton pump inhibitor or trimethoprim-sulfamethoxazole) during the corticosteroid taper was more common in the standard of care group, 9 (64%) versus rapid-taper group, 2 (15%), and was associated with longer time to renal recovery, 20 days (IQR 14–101) versus 13 days (IQR 7–34) in those that discontinued nephritis-causing medications. Fifteen (56%) of patients were rechallenged with ICIs, and only two (13%) developed recurrent nephritis. Conclusions: Patients with ICI-induced nephritis have excellent kidney outcomes when treated with corticosteroids that are tapered over 3 weeks.